Различия в организации сдвига в [1 1 0]- и [1 1 1]-монокристаллах меди при трении - Чумаевский А. В. Андрей Валерьевич; Лычагин Д. В. Дмитрий Васильевич; Тарасов С. Ю. Сергей Юльевич; Колубаев Е. А. Евгений Александрович; Беляев С. А. Сергей Александрович (2013, 2013)
Заглавие с экрана